Ancient Olive Presses and Oil Production In Cyrenaica (North-East Libya) - Buzaian, Ahmed (2022)
This masterly study presents the first comprehensive overview of olive oil production in Cyrenaica, North-East Libya, during the mid to late Roman period. The evidence collected by the author overturns previous assumptions about the small-scale of this industry and convincingly demonstrates its economic importance in both urban and rural settings. The typology and characteristics of Cyrenaican pressing elements and gazetteer of sites confirm this work as an essential reference volume for studies of ancient production and open up questions about the Cyrenaica’s role in producing olive oil for local, regional and Mediterranean markets.